FEATURES OF THE CHRONIC PAIN SYNDROME IN PATIENTS WITH RHEUMATOID ARTHRITIS AND MEDICAL DIAGNOSTIC TACTICS - M. A. Gromova; S. E. Myasoedova (Klinicist, 2016)
Objective: to establish features of a chronic pain syndrome disorders in patients with rheumatoid arthritis, to reveal correlation with psychoemotional disorders and to develop the differential approach to maintaining patients. Materials and methods. 101 patients at the age of 60.6 ± 11.8 years, 92 % of women, with reliable rheumatoid arthritis (American College of Rheumatology – ACR, 1987), were examined. The visual analog scale was used for an assessment of pain strength at the moment; the Van Korff’s questionnaire – for determination of pain strength at the moment and retrospectively for the last half a year with an assessment of disadaptation level and disability, ranging of a chronic pain syndrome on classes; the McGill Pain Questionnaire – for the characteristic of touchsensitive and emotional components of pain. Neuropathic pain was revealed by DN4 questionnaire. Anxiety and depression were determined by the Hospital Anxiety and Depression Scale (HADS). Fibromyalgia diagnosed by criteria of ACR, (1990). Results. Pain estimated by various scales and questionnaires varied from moderated to intensive. According to Van Korff’s questionnaire it was characterized by average level of disadaptation and easy disability that corresponded to the second class of chronic pain. The Rank pain index of the McGill Pain Questionnaire touch scale testified that pain was described by a smaller number of definitions on a touch scale than on emotional. This indicates a moderate impact of pain syndrome on a state of mind. Neuropathic pain is diagnosed for 37.3 % of patients with tunnel syndrome, mononeuritis and touch polyneuropathy. The secondary fibromyalgia is revealed for 2 % of patients with early rheumatoid arthritis of high activity. According to HADS anxiety and depression was revealed for 58 and 59 % of patients correspondingly. This demanded psychotherapeutic consultation and additional correction. We proposed the algorithm of diagnostic and medical tactics for rheumatoid arthritis patients with a chronic pain syndrome in therapeutic practice based on pain strength gradation, assessment of chronic pain syndrome variations, definition of anxiety and depression signs. All this allows to validate consultation of medical specialists and to differentiate treatment. Conclusions. The integrated approach to diagnostics of a chronic pain syndrome for rheumatoid arthritis allows to estimate pain strengths in dynamics of disease development, to reveal existence of pain variations, anxiety and depression. It enables usage of patient maintenance tactics and increases efficiency of treatment in therapeutic practice.